On Hölder continuity of solutions of doubly nonlinear parabolic equations with weight - Bonafede, S.; Skrypnik, I.I. (Український математичний журнал, 1999)
We prove the Hölder regularity of bounded weak solutions of doubly nonlinear degenerate parabolic equations with measurable coefficients.